2016
DOI: 10.1111/nmo.13000
|View full text |Cite
|
Sign up to set email alerts
|

Opioid analgesic use among patients presenting with acute abdominal pain and factors associated with surgical diagnoses

Abstract: Background The prevalence of chronic opioid use among non-cancer patients presenting with acute abdominal pain (AAP) is unknown. The aim was to characterize opioid use, constipation, diagnoses, and risk factors for surgical diagnoses among non-cancer patients presenting with AAP to an emergency department (ED). Methods We performed a retrospective, observational cohort study of all (n=16,121) adult patients (88% from Minnesota, Iowa and Wisconsin) presenting during 2014 with AAP. We used electronic medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Opioids have been used to treat pain for many years, including the treatment of visceral pain. [50][51][52]66 The analgesic effect of the GES method developed in this study was found to be mediated via the opioid mechanisms, particularly, via the µ-opioid receptor. Both naloxone and CTOP blocked GES-induced suppression of EMG responses to GD in the IA-treated rats.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Opioids have been used to treat pain for many years, including the treatment of visceral pain. [50][51][52]66 The analgesic effect of the GES method developed in this study was found to be mediated via the opioid mechanisms, particularly, via the µ-opioid receptor. Both naloxone and CTOP blocked GES-induced suppression of EMG responses to GD in the IA-treated rats.…”
Section: Discussionmentioning
confidence: 81%
“…It is unknown whether NGF plays a major role in the rodent model of FD and whether the possible GES effects on gastric hypersensitivity might be mediated via the NGF mechanism. Opioids, such as μ‐opioid receptor (OR), κ‐OR agonist, and δ‐OR antagonist (eluxadoline), have been used to treat pain, including visceral pain in gastrointestinal functional disorders, such as irritable bowel syndrome . We were also interested in possible analgesic effects of GES on opioid mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency evaluation is commonly sought for pain control and to evaluate for causes of abdominal pain that may be found in these patients, such as kidney stones and bowel obstruction. 75 …”
Section: μ Opioids Gi Symptoms and Syndromesmentioning
confidence: 99%
“…The indication for the opioids was abdominal pain in 21% (93/442) of these patients, suggesting that, despite the lack of evidence of efficacy or safety, μ opioid agonists are being prescribed for patients with non-cancer-related abdominal pain, which likely includes IBS. 75 …”
Section: μ Opioids Gi Symptoms and Syndromesmentioning
confidence: 99%